Facilitated Data Relay and Effects on Treatment of Severe Aortic Stenosis in Europe - Steeds, Richard P.; Lutz, Matthias; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Maly, Jiri; Aiello, Marco; Rudolph, Tanja K.; Lloyd, Guy; Santo Bortone, Alessandro; Hauptmann, Karl Eugen; Clerici, Alberto; et al. (Journal of the American Heart Association, 2019)
Background-Many patients with severe aortic stenosis are referred late with advanced symptoms or inappropriately denied intervention. The objective was to investigate whether a structured communication to referring physicians (facilitated data relay) might improve the rate and timeliness of intervention.
CRIS-Team WoS Importer:2019-11-15